Предмет: Математика,
автор: рецейпшн
как решить пример более рациенальным способом 109•9.17-5.37•72-37•9.17+1.2•72
Ответы
Автор ответа:
0
109*9,17-5,37*72-37*9,17+1,2*72= (109*9,17-37*9,17)-(5,37*72-1,2*72)=
9,17(109,9-37)-72(5,37-1,2)=9,17*72,9-72*4,17=( 5+4,17)*(72+0,9)-72*4,17=5*72+5*0,9+0,9*4,17+72*4,17-72*4,17=5*72+5*0,9+0,9*4,7=5*72+0,9*9,7=360+8,73=368,73
9,17(109,9-37)-72(5,37-1,2)=9,17*72,9-72*4,17=( 5+4,17)*(72+0,9)-72*4,17=5*72+5*0,9+0,9*4,17+72*4,17-72*4,17=5*72+5*0,9+0,9*4,7=5*72+0,9*9,7=360+8,73=368,73
Похожие вопросы
Предмет: Физика,
автор: vova1218
Предмет: Другие предметы,
автор: Аноним
Предмет: Музыка,
автор: iwbajwb
Предмет: Математика,
автор: m101a26t
Предмет: Химия,
автор: Karolina59